Sistema kalikreina kinina : inhibición del canal de potasio de la médula externa renal (ROMK) y gonadectomía - Guevara, Darío (2016)
The kalikrein kinin system (KKs) is a complex multi-enzymatic system involved in blood pressure regulation by its action on nitric oxide and prostaglandins. Previous reports from our laboratory have shown that high K+ intake diminish blood pressure, with a concomitant KKS activation and plasma aldosterone concentration increase. Similar effect was observed after gonads removal, suggesting a modulator role of sexual hormones in this context. These results led to us to explore different components in the renal aldosterone pathway, such as aldosterone receptor, epithelial sodium channel and renal outer medullary potassium channel (ROMK). ROMK channel participate in epithelial transport of NaCl at both ascending limb of Henle and distal convolute tubule (DCT) by generation of electrochemical gradient that allows luminal Na+ reabsorption driven by ATPase Na+/K+ located in the basolateral membrane.\nIn order to elucidate the role of both potassium and sexual hormones in the regulation of the SKK, ROMK channel inhibition by glibenclamide and prepuberal gonadectomy was performed, respectively.\nWe studied spontaneously hypertensive rats (SHR) of both sexes at the age of 12 weeks of life. In the last three days of the experiment, a half of the animals were treated with glibenclamide using 4 % glucose as vehicle and the other half received vehicle alone. A gonadectomy at weaning (4th week of life) was performed in a half of each group. Mean blood pressure, glomerular filtration rate, plasma aldosterone, urine volume and Na+ and K+ concentration and urine kalikrein activity (UKa) were measured. Renal medulla and cortex mRNA levels of KCJN1 and Atp1a1 genes, as well as of the Klk1 gene in renal cortex, were determined by real-time PCR.\nROMK channel inhibition increased urine Na+/K+ (0.55 ± 0.03 vs 1.34 ± 0.30, p < 0.05). This response was different according to sex and presence of gonads: urine K+ excretion decreased in intact male and ovariectomized rats while Na+ excretion increased in intact female rats.\nThe Na+ and K+ excretion showed a directly proportional relationship (r = 0.99; p < 0.05) and glibenclamide administration decreased the slope in a 54. 8\n% (p < 0.001). These results showed that ROMK channel inhibition prevents the recycling of K+ and results in a net increase of Na+ concentration in the final urine.\nGlomerular filtration rate increased post glibenclamide administration (0.51 ± 0.06 vs 0.76 ± 0,06 ml/min/100gPC p < 0.01) in the all treated groups without changes in blood pressure (121 ± 11 vs 127 ± 10 mmHg) nor plasma aldosterone (55 ± 12 vs 49 ± 10 pg/ml) levels.\nThe treatment with glibenclamide not modified UKa (24. 37 ± 3.96 vs 28.37 ± 4.25 nkat/day/100gPC) as well as Klk1 mRNA levels (1.10 ± 0.31 vs 1.75 ± 0.42).\nThe mRNA levels analysis showed that ROMK channel inhibition drastically inhibited the gene expression of Kcjn1 (1.29 ± 0.28 vs 0.32 ± 0.11, p < 0.01) and Atp1a1 (0.94 ± 0.23 vs 0.20 ± 0.02, p < 0.01) in renal medulla and also that this response was different according to the gonads presence.\nTaken together, these results show that urinary ion excretion was modified after channel ROMK blockade, according to the important role of the channel in the renal handling along the nephron. The significant changes found in mRNA levels in renal medulla suggest an inhibitory effect in Kcjn1 and Atp1a1 gene expression by ROMK channel blockage. Additionally, the GFR increase also indicates a role of ROMK in tubuloglomerular feedback modulation. The differences found after gonadectomy suggest that, at least in part, some role of sexual hormones in the electrolyte balance exists.\nThe UKa and Klk1 mRNA levels indicate a negligible role of ROMK in KKS modulation and future experiments will be designed to elucidate the involved mechanism in aldosterone and sexual hormones regulation of this system